The Diversity, Richness, and Potential Health and Ecological Role of the Fungal Aerosols in Attica, Greece - Angelina Metaxatos; Dafni Georgiadou; Dimitris Hatzinikolaou; Gediminas Mainelis (Aerosol and Air Quality Research)
Abstract Fungi play an important role in our environment, yet our knowledge of the outdoor mycobiome, is still very limited. Detecting and characterizing anemophilous fungi over extended periods in multiple locations can help elucidate the global distribution and diversity of aerial fungi. Given the scarcity and discontinuity of data on aerial mycobiome, we aimed to investigate the diversity, concentration, and variation of aerial fungal community in Attica, Greece. The results were used to determine the dominant fungal taxa and provide an extensive literature review to describe their potential impact on the ecosystem (ecological role) or latent role in public health and phytoprotection. Air samples were collected in various locations in Attica from 2019 to 2022 using passive REPS samplers and filters. We studied the taxonomy of aerial mycobiome by DNA extraction, purification, and a barcoded amplicon sequencing method. Overall, we isolated two main fungal phyla Ascomycota and Basidiomycota; in total, 195 species, 121 genera, 83 families, 45 orders, and 17 classes. The variability and diversity of aerial mycobiome differed between sites and campaigns. Richer aerial mycobiome diversity was found in less populated areas (Drafi and Lagonisi). We also isolated several fungal genera that, to the best of our knowledge, had not yet been reported from air samples, e.g., Basidioradulum, Coniella, Dothidea, Endoconidioma, Engyodontium, Fuscoporia, Myrothecium, Thanatephorus, Pyronema. Across all samples, the dominant fungal genera were Altenaria and Cladosporium, Nectria, Debaryomyces, and Aureobasidium, along with Malassezia and Epicoccum, among others. The results suggest the complexity and high variability of airborne fungal communities in Attica’s air. They also underscore the complexity and uncertainty of interpreting the biodiversity of airborne fungi solely based on barcoding analysis. Future research should integrate metagenomic and epidemiological data into the analysis of airborne fungal taxa to help elucidate their impact on public health and ecology.